Phylogenetic analysis of a region of mitochondrial cox-1 as a DNA barcode marker sequence of Gazella subgutturosa (Goitered gazelle) in Mongolia - M. Bayarlkhagva; B. Ulziibat; B. Gun-Aajav; D. Bazarsad; B. Damdingiin; E. Batmagnai (Animal Biodiversity and Conservation)
Gazella subgutturosa, a vulnerable species, is threatened by illegal hunting for meat and sport. The mitochondrial cytochrome c oxidase subunit 1 gene (cox-1) is used as a DNA marker to distinguish mammalian species for the investigation of illegal hunting. In this study, we sequenced a part of the cox-1 gene (709 bp) of six Mongolian G. subgutturosa individuals. Our DNA sequences were clustered in a clade of Gazella which is distinct from other clades of mammalian species in the phylogenetic tree. Our findings suggest that DNA sequences can be useful in the investigation of illegal hunting.